Pendampingan Penerapan Inovasi Layanan Paket Open Trip untuk Meningkatkan Minat Wisatawan pada PT. Romi Tour and Travel : Pengabdian - Amri, Adi Ihsan Syukri; Hamdiah, Hamdiah; Sari, Novita; Utami, Febby Nanda; Alissa, Evalina; Ramadani, Nanda Ayu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity aims to assist PT. Romi Tour and Travel in implementing innovative open trip service packages to increase tourist interest. The open trip concept combines participants from various backgrounds in a single travel package with predetermined schedules and destinations, offering more affordable prices and a unique social experience. The company’s main challenge is the low public interest in open trip packages compared to the more popular regular packages. The methods used in this program include preparation and needs analysis through observation, interviews, and document review, designing service innovations, and providing assistance in implementing promotional strategies through social media and partner networks. The results show an improvement in the company’s understanding of how to package open trip services more attractively and develop targeted promotional strategies. With consistent implementation, the open trip service is expected to become one of PT. Romi Tour and Travel’s flagship products in attracting public interest.